(untitled) - Popov, Konstantin (Moscow, 1969)
This book introduce aout Japan in the early period of her existence, geographical and historical survey. The discovery of Japan by Europeans and her external contacts. Infomation of Japan available abroad and development of scientific and geographical knowledge in the era of Japan's self-Isolation from the outside world...
Keywords: Địa lý,Geography; Nghiên cứu và giảng dạy,Study and teaching; Nhật Bản,Japan